Spirituals and the Birth of a Black Entertainment Industry - Graham, Sandra J. (Sandra Jean) (Book collections on Project MUSE., 2018)
In the first book-length treatment of postbellum spirituals in theatrical entertainments, Sandra Jean Graham mines a trove of resources to chart the spiritual's journey from the private lives of slaves to the concert stage. Graham navigates the conflicting agendas of those who, in adapting spirituals for their own ends, sold conceptions of racial identity to their patrons. In so doing they laid the foundation for a black entertainment industry whose artistic, financial, and cultural practices extended into the twentieth century.